Behavioral Intention to Adopt Lazada Services: an Extension of Unified Theory of Acceptance and use of Technology - Solihin, Dede; Ahyani, Ahyani; Aprilliani, Siti (Target : Jurnal Manajemen Bisnis, 2025)
The growth of e-commerce in Indonesia has driven changes in consumer behavior regarding online shopping. Lazada, as one of the main platforms, faces challenges in increasing user intention to adopt its services. This study aims to analyze the influence of four main constructs in the Unified Theory of Ac- ceptance and Use of Technology (UTAUT): performance expectancy, effort expectancy, social influence, and facilitating conditions, on behavioral intention in using Lazada services. The research method uses a quantitative approach by distributing questionnaires to 130 Lazada users in South Tangerang. Data analysis was carried out using Structural Equation Modeling (SEM) through SmartPLS. The results show that all UTAUT constructs significantly affect behavioral intention, with performance expectancy and facilitating conditions as the most dominant factors. Effort expectancy has an effect on new users, while social influence is stronger in young age groups who are active on social media. This study provides practical implications for e-commerce platform developers, especially Lazada, to improve performance expectancy, effort expectancy, social influence, and facilitating conditions to encourage user behavioral intention in adopting services, especially in the South Tangerang area. This finding also extends the literature on UTAUT-based digital technology adoption in the local Indonesian context.